The annotated Arabian nights : tales from 1001 nights - Horta, Paulo Lemos; Seale, Yasmine (Liveright Publishing Corporation, a division of W. W. Norton & Company, 2021)
"A groundbreaking translation-along with new commentary and hundreds of images-enhances this celebratory publication of the most famous story collection of all time. Starting in 1999 with the publication of The Definitive Annotated Alice, the Norton and Liveright annotated books have become the leading series of classic, illustrated works in the English language. The long-anticipated publication of The Annotated Arabian Nights extends this tradition with a strikingly modern translation-the first of Shahrazad's tales into English by a woman-as well as erudite notes that will illuminate the stories for both dedicated readers and newcomers. Yasmine Seale's translations from both Arabic and French capture the musicality and rhythm of the Nights' poetry and prose, while Paulo Lemos Horta's annotations wrestle with the extraordinarily complex origins and history of the stories, showing that, far from being inventions of French antiquarians or English explorers, they have clear antecedents in Arabic folklore and tradition. This stunningly illustrated edition selects core stories as well as treasured later additions such as "Aladdin" and "Ali Baba" to offer an unparalleled account of a cornerstone of world literature that can be treasured by children, students, and literature-lovers alike"--